Portrayal of Yorùbá Socio-cultural Heritage in the Practice of the Kegite Movement in Nigerian Tertiary Institutions - Hezekiah Olufemi Adeosun (Yoruba Studies Review)
This essay examines some aspects of the Yorùbá socio-cultural heritage portrayed in the practice of the Kegite Movement in Nigerian tertiary institutions. The Kegite is one of the student organizations in institutions of higher learning in Nigeria. Membership of the organization is open to only those who support the promotion and culture of palmwine drinking. Participant observation method of data collection which involved the researcher himself in the research setting was adopted. The paper relies on the socio-cultural theory for its analysis. Among the findings revealed in the study are that the Kegite Movement promotes aspects of the Yorùbá heritage which involved entrenching associations, teaching and enhancing morals through songs, method of selecting a king and his chiefs, use of language, and use of palmwine for entertainment purpose. Tis paper concludes that the Kegite Movement has been a virile organization towards the promotion of the Yorùbá socio-cultural heritage and in uniting the youth in Nigerian tertiary Institutions.